Experimental inoculation of a crow derived influenza A (H5N1) virus in chickens and its pathological and genetic characterization - DAS, B R; KUMAR, M; MURUGKAR, H V; NAGARAJAN, S; KUMAR, D SENTHIL; KALAIYARASU, S; KULKARNI, D D; TOSH, C (The Indian Journal of Animal Sciences, 2016)
We report the infectivity of a crow derived influenza A (H5N1) virus (A/crow/India/01TR01/2012) in chickens and its pathological and genetic characterization. Histopathological changes and immunohistochemistry staining of internal organs and skeletal muscle were consistent with influenza A virus infection. Real time RT-PCR and virus isolation results demonstrated the systemic spread of the virus in chickens with 100% mortality. Comparatively higher level of virus shedding was detected in oropharyngeal swab (7.63×106 viral RNA copy) than in cloacal swab (6.66 × 106 viral RNA copy). Concentrations of viral antigen in kidney, lungs, brain, spleen and large intestine were higher compared to pancreas and skeletal muscle. No genetic change was observed on interspecies transmission of the virus. The study revealed that the crow derived H5N1 virus is able to kill the poultry, underlining the need for close monitoring of presence of virus in poultry near crow roosting areas so that further transmission to other avian and mammalian hosts can be prevented.